Características zootécnicas de tilápias suplementadas com própolis bruta na dieta - JESUS, Grenei (2017)
Tilapia farming grows significantly throughout the national territory, mainly due to the market acceptance of tilapia fillet and the productive characteristics of this species. Although the productive chain of tilapia has shown great development in the last years, some obstacles are still persistent, like the high mortality rates and slow growth after allocation of the fingerlings or juveniles in the net tanks. The aim of this study was to evaluate the zootechnical characteristics of Nile tilapia (Oreochromis niloticus) fingerlings submitted to supplementation with crude green propolis. The animals were purchased at the commercial property Aquaminas, located in the city of São João da Mata, MG. Propolis was extracted from colonies of Apis mellifera bees, settled in an apiary in the Municipality of Cabo Verde, in the South of Minas Gerais, belonging to the Apiário Sol-Exportadora de Apiculas Company. A completely randomized design was used, with three treatments and three replications, with subdivision of plots. The experiment consisted of two phases. In the first phase, 1800 animals were used, masculinized, with an average weight of 1.5 ± 0.5g, distributed in six boxes of 500 liters, with aeration and constant water flow. In the second phase the plots were subdivided into 12 subplots and taken to net tanks. These tanks were randomly distributed in a conventional masonry tank (20 x 5 x 1 m) under ambient growing conditions. The water temperature, pH and dissolved oxygen were measured daily. Every two days the amount of total ammonia and nitrite were analyzed. The diets were elaborated with increased commercial diets with three levels of propolis concentrations (0, 1 and 2%). The rations used in the diet of the first phase were slurried and pelleted (1.8 mm), with 56% and 42% crude protein, respectively. In the next phase, to prepare the diet, pelleted ration with granulometry of 3 millimeters and 42% crude protein was used. Fish were fed four times daily in amounts of 10% of live weight. At the end of the experiment the following performance parameters were evaluated: standard length, total length, final weight, weight gain, apparent feed conversion and biomass. Fish consuming the feed supplemented with 1 and 2% crude green propolis showed higher growth. In view of the obtained data we conclude that the crude green propolis had efficacy as a growth promoter for Nile tilapia fingerlings.